Rola świadectwa w nowej ewangelizacji na przykładzie nowych ruchów eklezjalnych - Płusa, Sławomir (Verbum Vitae, 2015)
The issue of testimony in evangelization is today quite widely addressed, both in pastoral literature and in the formation of new movements within the Church. The teaching of the Church also raises this issue as the center of evangelization engagement. In this paper, we engage the problem of the role of testimony from the point of view of the evangelization movements, and its importance for the new evangelization. Our analysis of this topic first addresses the problem of the aim set by the new religious movements, and which is: the transformation of human life under the influence of an encounter with Christ and one’s witness to it. The testimony, which is intended to attract a man to Christ, is born of a certain Christian experience and is the result of a personal relationship with God. This origin of the testimony dictates the motivation of the witness. This motivation is included in the testimony of life, which is a tool for both pre-evangelization and evangelization. Testimony of one’s word has its center of gravity in the proclamation of the kerygma and the Gospel of grace. Fruitful testimony strengthens the identity of disciple-missionary and co-creates pastoral conversion of ecclesial communities. This is also an expression of the call of the new evangelization to the baptized who have lost a personal relationship with Christ and the Church.